2020
DOI: 10.3390/ijms22010069
|View full text |Cite
|
Sign up to set email alerts
|

Use of a Mixture of Polyols Based on Metasilicic Acid and Recycled PLA for Synthesis of Rigid Polyurethane Foams Susceptible to Biodegradation

Abstract: Two polyol raw materials were obtained in the conducted research, one based on metasilicic acid (MSA), the other based on poly(lactic acid) (PLA) waste. The obtained polyols were characterized in terms of their applicability for the production of rigid polyurethane foams (RPUFs). Their basic analytical properties (hydroxyl number, acid number, elemental analysis) and physicochemical properties (density, viscosity) were determined. The assumed chemical structure of the obtained new compounds was confirmed by pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 60 publications
0
7
0
Order By: Relevance
“…These outcomes showed that the hard polymer increasingly accumulated to make the domains in the polyurethane copolymer with an increase in hardness [ 34 ]. The Figure evidently depicts the impact of the extender on the polymer [ 46 ]. The amine groups (–NH), attached with hydrogen bonding, stretched at 3309, 3323, 3323, and 3315 cm −1 , in Figure 1 B–E, respectively [ 35 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…These outcomes showed that the hard polymer increasingly accumulated to make the domains in the polyurethane copolymer with an increase in hardness [ 34 ]. The Figure evidently depicts the impact of the extender on the polymer [ 46 ]. The amine groups (–NH), attached with hydrogen bonding, stretched at 3309, 3323, 3323, and 3315 cm −1 , in Figure 1 B–E, respectively [ 35 , 47 ].…”
Section: Resultsmentioning
confidence: 99%
“…The higher content of carbonyl groups, which increases the cohesive energy, makes polyurethane foams less flammable than polyethylene foams. The flammability of PUR foams depends on their type, degree of cross-linking, and the physical condition of the product [17,[45][46][47][48].…”
Section: Polyurethane Materialsmentioning
confidence: 99%
“…This gas has a much smaller thermal conductivity than air [ 25 , 26 ]. The size and distribution of these pores also play crucial roles in the material’s thermal insulation performance [ 27 ]. In general, RPUF exhibits the following basic characteristics [ 28 , 29 ]: Regularly arranged closed pores.…”
Section: Overview Of Thermal Insulation Materialsmentioning
confidence: 99%